THU0054 Utility of serological parameters in giant cell arteritis for predicting disease complications. (15th June 2017) - Lakota, K; Feichtinger, J; Burja, B; Kuret, T; Žigon, P; Rotar, Ž; Ješe, R; Sodin-Šemrl, S; Čučnik, S; Thallinger, G; Tomšič, M; Hočevar, A
Abstract : Background: Giant Cell Arteritis (GCA) is a systemic vasculitis affecting primarily large and medium sized arteries. Immediate high dose steroid treatment may prevent urgent complications, such as vision loss and cerebrovascular insults 1–3 . However, there is a clear lack of data on predicting serological markers and their association to clinical complications. Objectives: To investigate serological parameters that support clinicians in predicting complications in a large, clinically well-characterized set of untreated GCA patients at time of diagnosis. Methods: The study included 98 GCA patients (67% female) with a median (IQR) age 74.1 (67.3–78.8) years and a median (IQR) symptome duration time of 30 (20–90) days). Healthy blood donors (HDs, n=52, 61.5% female, median (IQR) age of 41.95 (20.4–63.1) years) served as controls. GCA complications studied were visual disturbances (including permanent loss of vision), relapses, peripheral artery involvement and claudication. Levels of 27 serum analytes were measured using Luminex xMAP Technology. Interleukin-6 (IL-6) and serum amyloid A (SAA) levels were tested using ELISA and nephelometry, respectively. Results: The highest, significantly elevated analytes in GCA vs. HDs were SAA (85-fold > HDs mean values), IL-23 (63-fold) and IL-6 (11-fold). IL-13, α-fetoprotein and MMP-2 were significantly decreased in GCA, while levels of IL-2, IL-17A and TNF-α were unchanged. PCA analysis revealed a signature analyte profile positioning towards the HD cluster. SAA, CRP, haptoglobin, ESR, thrombocyte # and matrix metalloproteinase-1 (MMP-1) all negatively associated with visual disturbances, confirming our previous data. Age showed significant association to permanent visual loss, with older patients being more affected 3 . SAA, CRP and ESR at presentation were found to be predictive of relapsing disease, while MMP-2 negatively associated with relapse. VCAM-1, α-fetoprotein, MARCO and IL-27 were all negatively associated with peripheral artery involvement. MMP-2 and MARCO showed positive association with claudication, while IL-18 was negatively associated. Conclusions: In our large study of untreated GCA patients we highlight the importance of using serological acute phase parameters, MMPs and other analytes for predicting complications. References: Weyand CM, Goronzy JJ. Medium- and large-vessel vasculitis. N Engl J Med 2003, 349:160–169. Nesher G: The diagnosis and classification of giant cell arteritis. J Autoimmun 2014, 48–49:73–75. Hocevar A et al. Do Early Diagnosis and Glucocorticoid Treatment Decrease the Risk of Permanent Visual Loss and Early Relapses in Giant Cell Arteritis: A Prospective Longitudinal Study. Medicine (Baltimore) 2016, 95:e3210. Disclosure of Interest: None declared